Validity Decision Letter Against Dismissal of State Civil Apparatus In Indonesia - Herman, Riyad Atmaja; Razak, Abdul; Ilyas, Anshori (Universitas Kristen Cipta Wacana, 2024)
This article examines the implications of the Joint Decree on Disrespectful Dismissal of the State Civil Apparatus, focusing on the dismissal of individuals who have completed their criminal sentences based on court decisions with permanent legal force (inkracht van gewijsde). Employing a Normative-Empirical research approach, the study was conducted in Palopo City, South Sulawesi Province, specifically at the Office of the Personnel and Human Resources Development Agency.The research identifies two key issues. Firstly, the Joint Decision Letter (Number 182/659/SJ, Number 15/2018, Number 153/Kep/2018) lacks specificity regarding sanctions against civil servants convicted of criminal offenses. This oversight poses a risk of maladministration actions, as it fails to address the potential consequences for non-compliance with the decree. Secondly, the article contends that the central government should not solely focus on dismissing civil servants convicted of corruption but also hold Personnel Supervisory Officials accountable for failing to enforce dismissals. This accountability serves as a crucial deterrent, discouraging selective application of sanctions and abuse of authority. The study underscores the importance of effective supervision and advocates for disciplinary training to instigate positive behavioral changes among employees, fostering a culture of adherence to legal mandates